2011
DOI: 10.1128/iai.00784-10
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Virulence in a Drosophila melanogaster Model

Abstract: Porphyromonas gingivalis has been implicated in the etiology of adult periodontitis. In this study, we examined the viability of Drosophila melanogaster as a new model for examining P. gingivalis-host interactions. P. gingivalis (W83) infection of Drosophila resulted in a systemic infection that killed in a dose-dependent manner. Differences in the virulence of several clinically prevalent P. gingivalis strains were observed in the Drosophila killing model, and the results correlated well with studies in mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 71 publications
(96 reference statements)
2
20
0
1
Order By: Relevance
“…A similar dose-dependent disease effect has been previously observed using a Drosophila melanogaster infection model albeit via a non-systemic route34. In addition, we observed extensive damage to the heart and surrounding tissue associated with pericardial oedemas.…”
Section: Discussionsupporting
confidence: 88%
“…A similar dose-dependent disease effect has been previously observed using a Drosophila melanogaster infection model albeit via a non-systemic route34. In addition, we observed extensive damage to the heart and surrounding tissue associated with pericardial oedemas.…”
Section: Discussionsupporting
confidence: 88%
“…Schneider et al suggested that Eiger signaling induced upon infection by some intracellular bacteria, which does not help fight infection, results in lethality via mechanisms that may be directly toxic or energetically wasteful (66). As heat-killed P. gingivalis kills Drosophila as readily as live P. gingivalis (37), nullification of the Imd pathway by the P. gingivalis capsule likely involves mechanisms that do not require bacterial viability. This study demonstrated that the C3/ā£ 2 M superfamily proteins Tep II and Tep IV are involved in the Drosophila immune response against P. gingivalis infection.…”
Section: Discussionmentioning
confidence: 99%
“…We recently developed a Drosophila melanogaster killing model for examining P. gingivalis-host interactions (37), and in the current study the killing model was used to characterize the host response to P. gingivalis infection. The Drosophila model has been widely used to examine the host responses to many other bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenicity of P. gingivalis has been investigated in a variety of experimental animal models such as rat, mouse, rabbit, drosophila, and cell models, showing complicated mechanisms of P. gingivalis -host interplay in the expansion of periodontal diseases (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%